Modernism in Late Ottoman Empire and in Early Turkey - ÅžimÅŸek, YÄ±lmaz (Mediterranean Journal of Social Sciences, 2012)
Methods in public administration have changed by the changes and improvements in society and its understanding ofadministration. These changes and improvements need new ideas and imaginations to break routine understanding ofadministration. A fashionable way of administration a century ago can be dated today unless it has dynamics rather thanbounded rules. This paper explores the experiments of modernity both in late Ottoman Empire and early Turkish Republic. Itfocuses in particular on continuity rather than change by the name of modernity.